Assessment of Variation in State Regulation of Generic Drug and Interchangeable Biologic Substitutions - Sacks, Chana A. (JAMA Intern Med, 2020)
IMPORTANCE: Brand-name drugs, including biologics, have been the primary source of increasing prescription drug spending in the US. Each state has drug product selection laws that regulate whether and how pharmacists can substitute prescriptions for brand-name drugs with more affordable equivalents, either small-molecule generic drugs or interchangeable biologics, but the details of these laws can vary. OBJECTIVE: To examine the variation in state drug product selection laws with regard to factors that may affect which version of a drug is dispensed. DESIGN, SETTING, AND PARTICIPANTS: A cross-sectional analysis was performed, using a legal database, to obtain information on state laws of all states plus Washington, DC, as they existed on September 1, 2019. EXPOSURES: Whether substitution was mandatory or permissive, patient consent was needed prior to substitution, patient notification of substitution was required independent of the drug’s packaging, and/or pharmacists were protected from special risk of liability for substitution. MAIN OUTCOMES AND MEASURES: For small-molecule and biologic drugs, descriptive statistics were generated for the 4 exposure variables. In addition, for small-molecule drugs, a generic substitution score with a maximum of 1 point was assigned for each exposure variable (range, 0-4 points), with higher scores indicating regulatory requirements limiting substitution. RESULTS: This cross-sectional analysis of the generic drug substitution regulations in the 50 US states and Washington, DC, found that for small-molecule drugs, 19 states required pharmacists to perform generic substitution; 7 states and Washington, DC, required patient consent; 31 states and Washington, DC, mandated patient notification independent of the drug’s packaging, and 24 states did not explicitly protect pharmacists from greater liability. Nine states and Washington, DC, had a generic substitution score for small-molecule drugs of 3 or higher, and 45 states had more stringent requirements for interchangeable biologic substitution, most commonly mandatory physician notification. CONCLUSIONS AND RELEVANCE: The findings of this study suggest that there is a need for optimizing state drug product selection laws to promote generic and interchangeable biologic substitution, which may help improve medication adherence and reduce drug spending.